THE TRIATRIAL HEART (COR TRIATRIATUM) - RARE ADULT CONGENITAL HEART DEFECT - Vladimir Kornovski; Sezgin Syuli; Vera Semerdzhieva; Iana Simova; Toni Vekov (Peytchinski Publishing, 2022)
Background: Cor triatriatum is a rare congenital cardiac malformation. Prevalence is only around 0.1% of the diagnosed congenital cardiovascular malformations. Historically the prevalence has been described around 0.4% in autopsies in patients with congenital heart disease. It is characterized by the presence of a membrane, usually, the endocardium and fibro-muscular tissue within one of the atrial chambers, dividing it into two, thereby giving the appearance of three atrial chambers. Case report: A 72-year-old patient presented to our cardiac surgery department with complaints of rhythm disorders, heart palpitations and shortness of breath. The patient has a history of mitral valve pathology. During the last six months, she has had a progression of these heart failure clinical manifestation and is reffered to our institution for mitral valvle surgery after selective coronary angiography. The echocardiography showed an abnormal membrane dividing the left atrium, and the diagnosis of cor triatriatum was fully made via transesophageal echocardiography. There were associated significant mitral valve and tricuspid valve regurgitations. Conclusion: CTS/cor triatrium sinister/ is a congenital acyanotic heart disease which rarely presents during adulthood. The symptoms in adults are similar to those of mitral valve stenosis. The prognosis of the patient with CTS depends on the size of the fenestration into the fibromuscular membrane. Corrective surgery is a treatment of choice for CTS.